ITQS, Common Fisheries Policy, and stakeholders’ perceptions - Borges, Maria Rosa (2021)
ITQS, Common Fisheries Policy, and stakeholders’ perceptions - Rights Based Management (RBM) schemes have already been experimented with in specific fisheries and locations. The lessons given by these experiences are fundamental to explore the feasibility of such tools and their social, economic, and environmental impacts. In this paper we analyze the possibility of introducing a more focused approach on rbm, in the form of Individual Transferable Quotas (ITQS) in the Common Fisheries Policy. Using Stakeholders Analysis, we analyze and report the different perceptions of the Portuguese stakeholders facing this situation. We conclude that the intro duction of itqs tends to increase market concentration in the sector, triggering serious social problems for locals.